2014
DOI: 10.1021/jp510777c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Non-Condon Effects in a Covalent Tetracene Dimer: How Important Are Vibrations in Determining the Electronic Coupling for Singlet Fission?

Abstract: Singlet fission (SF) offers opportunities for wavelength-selective processing of solar photons with an end goal of achieving higher efficiency inexpensive photovoltaic or solar-fuels-producing devices. In order to evaluate new molecular design strategies and for theoretical exploration of dynamics, it is important to put in place tools for efficient calculation of the electronic coupling between single-exciton reactant and multiexciton product states. For maximum utility, the couplings should be calculated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
129
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(136 citation statements)
references
References 72 publications
7
129
0
Order By: Relevance
“…For the estimated BT1 reorganization energy mentioned above (λ tot ≈ 0.5 eV) we found an effective coupling for SF (V eff ) on the order of 5 meV. 48 In light of the experimental data presented herein, this now appears to be a modest overestimate by ∼1 order of magnitude. Application of Marcus theory with V eff = 5 meV, λ tot = 0.5 eV, and ΔE SF = 0.052 eV would suggest a time constant for forming the 1 TT of 630 ps, ∼100 times faster than our observation of 70 ns.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…For the estimated BT1 reorganization energy mentioned above (λ tot ≈ 0.5 eV) we found an effective coupling for SF (V eff ) on the order of 5 meV. 48 In light of the experimental data presented herein, this now appears to be a modest overestimate by ∼1 order of magnitude. Application of Marcus theory with V eff = 5 meV, λ tot = 0.5 eV, and ΔE SF = 0.052 eV would suggest a time constant for forming the 1 TT of 630 ps, ∼100 times faster than our observation of 70 ns.…”
Section: Introductionmentioning
confidence: 52%
“…In theoretical work we showed that diabatic electronic coupling for conversion from a dimer (AB) state S 1 S 0 or S 0 S 1 (or a superposition of these) to 1 TT will be zero as long as the molecule maintains a symmetry plane passing through both chromophores as it does in the C 2v ground state. 48 The effect is due to orbital symmetry (we explored this with a frontier orbital basis set) and is true for both direct and charge-transfer mediated pathways. Diabatic coupling for SF can emerge through vibrations that break this plane of symmetry; however, one might intuit that rates of S 1 to 1 TT conversion should be small in BT1 compared to systems where such coupling is nonzero at the static geometry of the ground state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 The resulting model Hamiltonians have been used to benchmark approximate methods in more recent studies. 16 However, our ASD method was not applicable to covalently linked chromophores in previous works. This was mainly due to the difficulty in finding appropriate ASD subspaces.…”
Section: Introductionmentioning
confidence: 93%